Karakter Pemimpin Perspektif Al Qur`an - Muhammad Fuad Ikhwansyah; Muhammad Teguh Ciptadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Palangkaraya, 2025)
Human in its creation is as Khalifah (leader) on this earth, as the main human being has character to be seeded in directing or in terms of fostering the morals of the led. Leadership in Islam is a very complex scope, ranging from the social structure of the organisation, strategies in directing, exemplary, and to faith. The expectation in a leadership is a goal of benefit, both for the leader and the led. The verses of the Qur'an are very concentrated on discussing the criteria of leadership which is raised in several main characteristics. The first trait is that the leader is characterised as Khalifah. The second trait is Imamah. The third trait is Ulul Amr. The scope of the Qur'anic verses that discuss Khalifah, Imamah, Ulul Amr are (QS. Shad [38]: 26), (QS. Al Baqarah [2]: 124), (QS. An Nisa [4]: 59), (QS. An Nisa [4]: 83). The verses include the verses of Makkiyah and Madaniyah. Furthermore, these verses will be described with the approach of Tafsir Maudhu`I (Thematic). The aspect of Asbabun Nuzul (the causes of the revelation of the verse) becomes an important part in describing the background of the verse. Similarly, the verse will be described in relation to other verses (Munasabah). From these verses emerges the character of leaders who are faithful, trustworthy, just, and have a personality like the apostle (Rasuli) with quite strict conditions.